Reading Comprehension and School Performance - GARCÍA GARCÍA, MIGUEL ÁNGEL; ARÉVALO DUARTE, MAYRA ALEJANDRA; HERNÁNDEZ SUÁREZ, CÉSAR AUGUSTO (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This study is aimed to determine the relationships between the level of reading comprehension of the students and their academic performance. A descriptive study and a correlational statistical analysis are carried out. The Reading Competency Test for High School was applied to students of both sexes among ages of 13 and 14 of the ninth grade of basic education of a public educational institution. From the descriptive analysis the students present difficulties at a textual, inferential and contextual level; in the correlation- al analysis of the data of the different subjects (natural sciences, social sciences, Spanish language and mathematics) they have a positive significant correlation, but it does not necessarily mean the existence of a cause-effect relationship